The prevalence of patients suffering from chronic spontaneous urticaria, in whom omalizumab cannot be stopped even after six years - Schichter-Konfino, V.; Mubariki, R.; Toubi, E.; Vadasz, Z. (Frontiers in Allergy, 2024)
BackgroundOmalizumab (OMA) was the first FDA-approved biological drug for severe chronic spontaneous urticaria (CSU), and until today is the only beneficial and truly safe one. The objectives were: To assess the prevalence of CSU patients in whom OMA cannot be stopped over time. We also asked if biomarkers (e.g., anti-TPO antibodies and total IgE) could assist in anticipating this issue.MethodsWe used our prospective registry of 93 patients, which included CSU disease duration, the onset of OMA treatment, Urticaria Activity Score (UAS7) during follow-up, co-morbidities, serum IgE levels and the presence of anti-TPO antibodies. Finally, we assessed the response to OMA during a period of six years.ResultsOut of the 93 treated CSU patients, OMA was stopped in ten patients after six months being defined as failures. In another ten patients, OMA was discontinued after 2–4 years of therapy, achieving a remission. Seventy-three patients are still treated between 2 and 6 years, having different degrees of response. Of these, in thirty-eight (52%) patients, we could not stop OMA even after six years due to CSU relapses. The prevalence of lower serum IgE levels and anti-TPO antibody positivity was significantly higher in CSU patients in whom OMA could not be stopped.ConclusionThis is the first study where OMA-treated CSU patients were followed up to six years. In half of them, long-term therapy of six years is still required.